Mutation screening of the EXT1 and EXT2 genes in patients with hereditary multiple exostoses. - Philippe, C; Porter, D; Emerton, M; Wells, D; Simpson, A; Monaco, A (1997)
Hereditary multiple exostoses (HME), the most frequent of all skeletal dysplasias, is an autosomal dominant disorder characterized by the presence of multiple exostoses localized mainly at the end of long bones. HME is genetically heterogeneous, with at least three loci, on 8q24.1 (EXT1), 11p11-p13 (EXT2), and 19p (EXT3). Both the EXT1 and EXT2 genes have been cloned recently and define a new family of potential tumor suppressor genes. This is the first study in which mutation screening has been performed for both the EXT1 and EXT2 genes prior to any linkage analysis. We have screened 17 probands with the HME phenotype, for alterations in all translated exons and flanking intronic sequences, in the EXT1 and EXT2 genes, by conformation-sensitive gel electrophoresis. We found the disease-causing mutation in 12 families (70%), 7 (41%) of which have EXT1 mutations and 5 (29%) EXT2 mutations. Together with the previously described 1-bp deletion in exon 6, which is present in 2 of our families, we report five new mutations in EXT1. Two are missense mutations in exon 2 (G339D and R340C), and the other three alterations (a nonsense mutation, a frameshift, and a splicing mutation) are likely to result in truncated nonfunctional proteins. Four new mutations are described in EXT2. A missense mutation (D227N) was found in 2 different families; the other three alterations (two nonsense mutations and one frameshift mutation) lead directly or indirectly to premature stop codons. The missense mutations in EXT1 and EXT2 may pinpoint crucial domains in both proteins and therefore give clues for the understanding of the pathophysiology of this skeletal disorder.